ANTECEDENT KEPUTUSAN PEMBELIAN ONLINE - Rahmawati, Siti Annisa; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2013)
The user internet in Indonesia have been increasing constantly each year. One of the internet user is for online purchasing. This online purchasing is not only caused by attractive user of its website but also affected by the special offer of products from this website. This study is to seek for antecedents of this online purchase decison.The data was collected by disseminating questionnaires via internet and face to face method. The respondents were internet users. The sampling method was purposive sampling. The model developed was two stage namely 1) attitude towards use is a function of trust and professionalism, and 2) online decision is a function of trust, professionalism and attitude towards use.The results show that all regression coefficients were significant. The independent variable that has the most influence toward the dependent ones is trust (X1) professionalism (X2) and attitude toward use (Y1) respecively. The t-test result show the entire of independent variables (trust, professionalism, and attitude toward use) have positive influence and significant toward the dependent variable that is the purchasing decision (Y2). The model showed a very good fit.it implies that all variables played impact includes in online purchasing.